Insurgency in the modern world - O'Neill, Bard E.; Heaton, William R.; Alberts, Donald J. (Routledge, 2018)
While all instances of insurgency have elements in common, the circumstances that precipitate them and the forms they take vary immensely. The editors of this book synthesize the literature on insurgency to provide an analytical framework that outlines categories of insurgent movements (secessionist, revolutionary, restorational, reactionary, conse